Exchange-rate stability causes deterioration of the productive sphere and destabilizes developing economies - Arturo Huerta González (Levy Economics Institute of Bard College, 2024)
For Matías Vernengo and Esteban Pérez Caldentey (2020), the MMT literature overemphasizes the choice of the exchange rate regime and the relevance of a flexible exchange rate regime, as well as the ultimate effect of that choice upon the policy space. In addition, they argue that the role of capital flows is underexplored, and that the relevance of the balance-of-payments constraint is often underestimated. Vernengo and Pérez's criticism fails to consider that exchange-rate flexibility makes it possible to use flexible fiscal and monetary policies as well, to boost growth and employment, and to reduce the balance-of-payments constraint.
Keywords: E42; E43; E44; O23; O24; 330; Capital Mobility; Currency; Exchange Rate; Financial Sector; Fiscal Policy; Foreign; Exchange Policy; Government Spending; Interest Rates; Monetary Policy; Real Activity